Cbfb Regulates Bone Development by Stabilizing Runx Family Proteins. (April 2015) - Qin, Xin; Jiang, Qing; Matsuo, Yuki; Kawane, Tetsuya; Komori, Hisato; Moriishi, Takeshi; Taniuchi, Ichiro; Ito, Kosei; Kawai, Yosuke; Rokutanda, Satoshi; Izumi, Shinichi; Komori, Toshihisa
ABSTRACT: Runx family proteins, Runx1, Runx2, and Runx3, play important roles in skeletal development. Runx2 is required for osteoblast differentiation and chondrocyte maturation, and haplodeficiency of RUNX2 causes cleidocranial dysplasia, which is characterized by open fontanelles and sutures and hypoplastic clavicles. Cbfb forms a heterodimer with Runx family proteins and enhances their DNA‐binding capacity. Cbfb‐ deficient ( Cbfb −/− ) mice die at midgestation because of the lack of fetal liver hematopoiesis. We previously reported that the partial rescue of hematopoiesis in Cbfb −/− mice revealed the requirement of Cbfb in skeletal development. However, the precise functions of Cbfb in skeletal development still remain to be clarified. We deleted Cbfb in mesenchymal cells giving rise to both chondrocyte and osteoblast lineages by mating Cbfb fl/fl mice with Dermo1 Cre knock‐in mice. Cbfb fl/fl/Cre mice showed dwarfism, both intramembranous and endochondral ossifications were retarded, and chondrocyte maturation and proliferation and osteoblast differentiation were inhibited. The differentiation of chondrocytes and osteoblasts were severely inhibited in vitro, and the reporter activities of Ihh, Col10a1, and Bglap2 promoter constructs were reduced in Cbfb fl/fl/Cre chondrocytes or osteoblasts. The proteins of Runx1, Runx2, and Runx3 were reduced in the cartilaginous limb skeletons and calvariae of Cbfb fl/fl/Cre embryos compared with the respective protein in the respective tissue of Cbfb fl/fl embryos at E15.5, although the reduction of Runx2 protein in calvariae was much milder than that in cartilaginous limb skeletons. All of the Runx family proteins were severely reduced in Cbfb fl/fl/Cre primary osteoblasts, and Runx2 protein was less stable in Cbfb fl/fl/Cre osteoblasts than Cbfb fl/fl osteoblasts. These findings indicate that Cbfb is required for skeletal development by regulating chondrocyte differentiation and proliferation and osteoblast differentiation; that Cbfb plays an important role in the stabilization of Runx family proteins; and that Runx2 protein stability is less dependent on Cbfb in calvariae than in cartilaginous limb skeletons. © 2014 American Society for Bone and Mineral Research.